Évaluation de l'effet antimicrobien et antioxydant de l'huile essentielle de romarin (rosmarinus officinalis L.) - SALAH, SARA (My University, 2024)
The present work was carried out within the framework of the valorization of the Algerian Mediterranean flora and more particularly, of plant species, namely, Rosmarinus officinalis L., by analyzing their chemical composition and their toxicity. As well as that of their essential oils, but also, by evaluating some of their biological properties such as, antimicrobial, antioxidant activity. Rosemary essential oil is obtained from the leaves and flowers of the Rosmarinus officinalis plant. L. by a steam distillation process, represents a yield of around 0.62%. The physical indices of the plant's essential oil show great similarity. They comply with those given by AFNOR. The acid number of the oil was 2.24 and the ester number was 325.10. The chemical study of this essential oil by CPG revealed its richness in 15 compounds exhibiting a total of approximately 92.56% of identified compounds. Antibacterial activity was determined by the agar diffusion method. This activity was tested against 4 bacterial strains and a fungus. The greatest antibacterial activity was expressed on staphylococcus with an inhibition diameter of 21mm. A significant rate of antifungal activity against candida albicans with a diameter of 22mm. The results obtained show that this EO has a positive effect on microorganism strains. The antioxidant capacity was measured using a free radical scavenging activity assay using 2,2-diphenyl-1-picrylhydrazyl (DPPH). According to the results, the oil essential has a moderate anti-radical and antioxidant potential, with 64% for the plant cultivated in the Mostaganem region. In Conclusion, This essential oil has beneficial biological activities in therapeutic applications in traditional medicine, in aromatherapy, in cosmetics, in cooking, because of its multiple benefits for health and well-being.
Keywords: Rosmarinus officinalis L; essential oils; Antioxidants; DPPH; Ascorbic acid